2021
DOI: 10.1111/pcn.13306
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the mental health symptoms during the Covid‐19 pandemic in Southeast Asia

Abstract: Aims:The Covid-19 pandemic has had a substantial impact on the mental health of the general public and high-risk groups worldwide. Due to its proximity and close links to China, Southeast Asia was one of the first regions to be affected by the outbreak. The aim of this systematic review was to evaluate the prevalence of anxiety, depression and insomnia in the general adult population and healthcare workers (HCWs) in Southeast Asia during the course of the first year of the pandemic.Methods: Several literature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 77 publications
0
19
3
1
Order By: Relevance
“…Explanatory factors of the high heterogeneity and moderators were roughly similar to those in the general population such as different scales and cutoffs (e.g., [ 33 ]), non-random sampling or sample (size) differences (e.g., [ 34 , 36 ]), region of study (e.g., [ 74 , 135 ]), and quality or risk of bias scores of studies [ 9 , 42 ]. Similarly, prevalence rates were higher in studies with larger proportions of female versus male workers, medical versus non-medical professionals, frontline versus non-frontline workers, and nurses versus doctors (e.g., [ 27 , 41 , 56 , 97 , 102 , 105 , 107 , 123 ]). Prevalence rates of above cut-off PTSD level were related to COVID-19 mortality rate [ 60 ] and inconsistently to age (e.g., higher in older [ 61 , 143 ] or in younger health professionals [ 138 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Explanatory factors of the high heterogeneity and moderators were roughly similar to those in the general population such as different scales and cutoffs (e.g., [ 33 ]), non-random sampling or sample (size) differences (e.g., [ 34 , 36 ]), region of study (e.g., [ 74 , 135 ]), and quality or risk of bias scores of studies [ 9 , 42 ]. Similarly, prevalence rates were higher in studies with larger proportions of female versus male workers, medical versus non-medical professionals, frontline versus non-frontline workers, and nurses versus doctors (e.g., [ 27 , 41 , 56 , 97 , 102 , 105 , 107 , 123 ]). Prevalence rates of above cut-off PTSD level were related to COVID-19 mortality rate [ 60 ] and inconsistently to age (e.g., higher in older [ 61 , 143 ] or in younger health professionals [ 138 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of depression, anxiety and sleep disorders were 36, 34, and 52%, respectively in Spanish medical personnel (37); 37, 23, and 34% in Latin America (38); 55, 51, and 28% in Africa (39); 34%, 46% (40), and 40% (41) in Eastern Europe. And the prevalence of depression, anxiety and sleep disorders among health-care workers in south-east Asia were generally lower than other regions during the pandemic, which were 14, 23, and 18% (42), respectively. Therefore, the prevalence of mental health symptoms during the COVID-19 pandemic is not homogeneous across different regions.…”
Section: Discussionmentioning
confidence: 90%
“…Another recent study (n = 155) reported 35.6% moderate to severe depressive symptoms during the COVID pandemic in Kosovo [8]. This is well above the mean found in Southeast Asia (16%) [9] but still below the mean found in Africa (45%) [10].…”
Section: Introductionmentioning
confidence: 80%